SOCIO-ECONOMIC HISTORY: THE TREND IN THE STUDY ON INDONESIAN HISTORY 1950-1980S - Soegijanto Padmo (Humaniora, 1994)
In the early years of Indonesian independence, the study of Indonesia's recent history tended to be dominated by scholars who emphasized political and cultural themes in their studies. There was a need to explain those developments of the colonial period which underlay some of the most important features of newly independent Indonesia. About two decades ago a new dimension began be opened up in the Indonesia social sciences when a group of historians and social scientists carried out studies of socioeconomic history of certain localities on Indonesia. The development of the social sciences in Indonesia was also leading to a better understanding of rural society. This new focus on Indonesian historical and socio-economic studies, directed especially at agricultural and socialaspects, was very appropriate.